Argipressin for prevention of blood loss during liver resection: a study protocol for a randomised, placebo-controlled, double-blinded trial (ARG-01) - Aldina Pivodic; Magnus Rizell; Kristina Svennerholm; Ellinor Wisén; Andreas Kvarnström; Lena Sand-Bown; Sven-Erik Ricksten (BMJ Open)
Introduction Liver resection carries a high risk for extensive bleeding and need for blood transfusions, which is associated with significant negative impact on outcome. In malignant disease, the most common indication for surgery, it also includes increased risk for recurrence of cancer. Argipressin decreases liver and portal blood flow and may have the potential to reduce bleeding during liver surgery, although this has not been explored.Method and analysis ARG-01 is a prospective, randomised, placebo-controlled, double-blinded study on 248 patients undergoing liver resection at Sahlgrenska University Hospital, Sweden. Patients will be randomised to one of two parallel groups, infusion of argipressin or normal saline administered peroperatively. The primary endpoint is peroperative blood loss. Secondary outcomes include need for blood transfusion, perioperative variables, length of hospital stay, the inflammatory response, organ damage markers and complications at 30 days.Ethics and dissemination The study is enrolling patients since March 2022. The trial is approved by the Swedish Ethical Review Authority (Dnr 2021-03557) and the Swedish Medical Product Agency (Dnr 5.1-2021-90115). Results will be announced at scientific meetings and in international peer-reviewed journals.Trial registration number ClinicalTrials.gov, NCT05293041 and EudraCT, 2021-001806-32